2023
DOI: 10.3390/toxics11070578
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Overexpression Alters Autophagy Levels and Slows Sodium Arsenite-Induced Hepatic Stellate Cell Fibrosis

Abstract: Exposure to inorganic arsenic remains a global public health problem. The liver is the main target organ, leading to arsenic-induced liver fibrosis. Phosphatase and tensin homology deleted on chromosome ten (PTEN) may participate in arsenic-induced liver fibrosis by regulating autophagy, but the exact mechanisms remain unclear. We established a mouse model of arsenic poisoning through their drinking water and a fibrosis model using the human hepatic stellate cell line LX-2 through NaAsO2 exposure for 24 h. Mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Furthermore, Meng D [43] noted that carvedilol mitigates liver fibrosis by inhibiting autophagy and promoting apoptosis in HSCs. Previous research by our group has revealed that inorganic arsenic can induce autophagy, thereby promoting liver fibrosis [44]. Recent studies suggest that SLC7A11 may be involved in the autophagy process.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, Meng D [43] noted that carvedilol mitigates liver fibrosis by inhibiting autophagy and promoting apoptosis in HSCs. Previous research by our group has revealed that inorganic arsenic can induce autophagy, thereby promoting liver fibrosis [44]. Recent studies suggest that SLC7A11 may be involved in the autophagy process.…”
Section: Discussionmentioning
confidence: 90%